2012
DOI: 10.1029/2012ja017917
|View full text |Cite
|
Sign up to set email alerts
|

Bounce‐averaged advection and diffusion coefficients for monochromatic electromagnetic ion cyclotron wave: Comparison between test‐particle and quasi‐linear models

Abstract: [1] The electromagnetic ion cyclotron (EMIC) wave has long been suggested to be responsible for the rapid loss of radiation belt relativistic electrons. The test-particle simulations are performed to calculate the bounce-averaged pitch angle advection and diffusion coefficients for parallel-propagating monochromatic EMIC waves. The comparison between test-particle (TP) and quasi-linear (QL) transport coefficients is further made to quantify the influence of nonlinear processes. For typical EMIC waves, four non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
122
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(124 citation statements)
references
References 104 publications
(189 reference statements)
2
122
0
Order By: Relevance
“…But scattering by each type of wave alone cannot completely explain the observed MeV electron dynamics. On the other hand, scattering by EMIC waves alone [Thorne and Kennel, 1971;Summers and Thorne, 2003;Sandanger et al, 2007;Su et al, 2012;Blum et al, 2015] usually entails fast precipitation of only a small part of the MeV electron population Usanova et al, 2014]. On the other hand, scattering by EMIC waves alone [Thorne and Kennel, 1971;Summers and Thorne, 2003;Sandanger et al, 2007;Su et al, 2012;Blum et al, 2015] usually entails fast precipitation of only a small part of the MeV electron population Usanova et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But scattering by each type of wave alone cannot completely explain the observed MeV electron dynamics. On the other hand, scattering by EMIC waves alone [Thorne and Kennel, 1971;Summers and Thorne, 2003;Sandanger et al, 2007;Su et al, 2012;Blum et al, 2015] usually entails fast precipitation of only a small part of the MeV electron population Usanova et al, 2014]. On the other hand, scattering by EMIC waves alone [Thorne and Kennel, 1971;Summers and Thorne, 2003;Sandanger et al, 2007;Su et al, 2012;Blum et al, 2015] usually entails fast precipitation of only a small part of the MeV electron population Usanova et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Whistler mode hiss (inside the plasmasphere) or chorus (outside the plasmasphere) waves alone induce relatively slow losses of whole populations of relativistic electrons, with lifetimes L > 2 − 5 days ("lifetimes" denoting loss time scales of the entire particle population up to equatorial pitch angles 0 ≈ 90 ∘ ) [Artemyev et al, 2013;Ni et al, 2013;Ma et al, 2015;Artemyev et al, 2016;Orlova et al, 2016]. This occurs because the upper cutoff frequency of quasi-parallel EMIC waves of realistic amplitudes (∼0.1-1 nT, such that nonlinear effects remain weak [Su et al, 2012]) is often sufficiently far from the corresponding ion gyrofrequency Zhang et al, 2016b] to prevent these waves from resonantly scattering MeV electrons at high equatorial pitch angles ( 0 > 0,max (EMIC) ∼ 45 ∘ -70 ∘ ) Usanova et al, 2014;Mourenas et al, 2016] where most of the MeV electron population is found [e.g., Ni et al, 2015]. This occurs because the upper cutoff frequency of quasi-parallel EMIC waves of realistic amplitudes (∼0.1-1 nT, such that nonlinear effects remain weak [Su et al, 2012]) is often sufficiently far from the corresponding ion gyrofrequency Zhang et al, 2016b] to prevent these waves from resonantly scattering MeV electrons at high equatorial pitch angles ( 0 > 0,max (EMIC) ∼ 45 ∘ -70 ∘ ) Usanova et al, 2014;Mourenas et al, 2016] where most of the MeV electron population is found [e.g., Ni et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…25,[31][32][33] But in the second-order resonance given by d 2 g=dt 2 ¼ 0, which enables the stable trapping of a resonant electrons, 34 this centripetal acceleration force plays an important role. Although this centripetal term had already been included in some numerical studies, 14,16 but was usually not taken into account in theoretical analysis. 1,26,29,[34][35][36][37][38] The motion of phase trapped electrons is dominated not by the ambient magnetic field, but by the wave field, 26,39 which enables the particle parallel velocity to follow the resonant velocity all the way in the wave field.…”
Section: Effect Of Wave Centripetal Force In Phase Trappingmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] However, the quasilinear approach inherently neglects nonlinear effects arising from the interactions between radiation belt electrons and various magnetospheric waves, and these nonlinear effects have been studied using test-particle simulations. [14][15][16][17] The motion of charged particles in an electromagnetic field is governed by the Lorentz force, and thus can be modeled by integrating the Lorentz equation directly. 18 But it is often more instructive and computationally economical to gyro-average the equations so that numerical integration can proceed on time scales comparable to the gyro-period.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown in 333 the past that for EMIC waves with amplitude of several nT nonlinear effects such as phase 334 bunching and phase trapping may play important role and cause significant deviations form theresults of quasi-linear model [e.g. Albert and Bortnik, 2009;Su et al, 2012;. Thus, the 336 assumption of non-thermal motion of plasma particles, as well as quasi-linear approach, has to 337 be challenged in our future studies.…”
Section: General Remarks 319mentioning
confidence: 99%